Weighted Multi-Threaded Process Fair Operating System Scheduler - Siang, Wong Chee (2009)
In this dissertation, an empirical analysis was carried out to illustrate the issue of fairness and expose the weakness of the thread-fair scheduling algorithm where software developers could take advantage by spawning many additional threads in order to obtain more CPU resources.